The culturally grounded leadership dynamic : promoting Māori success in English-medium state boys' schools in Aotearoa : a thesis presented in partial fulfilment of the requirements for the degree, Master of Education (Educational Administration and Leadership) at Massey University, Manawatū, New Zealand - Haines, Greg (Massey University, 2026)
This exploratory study investigates the relationship between leadership action and sustained school success among male Māori learners in Aotearoa New Zealand. Although the national commitment demands that Māori students achieve success as Māori, research has yet to explore the specific culturally grounded leadership dynamic required to drive genuine institutional transformation. English-medium single-sex boys' secondary schools achieve higher University Entrance outcomes for Māori boys than English-medium co-educational secondary schools; the leadership strategies driving this success remain largely undocumented. A qualitative comparative multi-site case study design, grounded in a Te Tiriti-led application of Cunningham's (1998) Māori-centred framework, was employed. The researcher collected data through in-depth interviews with senior leaders, including two Headmasters, and Year 13 Māori students from three boys' secondary schools. The study found that effective leadership establishes this dynamic by integrating Te Ao Māori principles such as mana and whanaungatanga into formal institutional structures. The study identified strategies to more closely align cultural identity with educational excellence, thereby mediating the perceived conflict between peer acceptance and academic success. Academic achievement statistics provide the empirical context for this study, grounding the qualitative analysis of leadership strategies. The thesis concludes by presenting a contextualised model of effective strategy that defines this successful dynamic, offering an empirically-based guide for institutional transformation and policy in Aotearoa New Zealand.
Keywords: 390403 Educational administration, management and leadership; 450811 Te mātauranga Māori i roto i te mātauranga (Mātauranga Māori in education)